Satisfied customers they're worth the effort. (Video Communicators., 1990)
Winning new customers is an expensive business so keeping our existing customers satisfied is very important. Unfortunately we don't always know when our customers are unhappy because in reality only 5% of customers actually complain. We must make it easy for customers to provide us with feedback even if it is in the form of complaints, to improve our overall service.
Keywords: Consumer satisfaction; Customer relations; Customer service